2023
DOI: 10.1002/jsfa.12815
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian consumers' food safety beliefs and trust issues in the age of COVID‐19: evidence from an online survey in 15 countries

Abstract: BACKGROUNDThis investigation provides an important insight into Eurasian consumers' food safety beliefs and trust issues influenced by the COVID‐19 pandemic. An online survey was conducted in 15 European and Asian countries involving more than 4000 consumers.RESULTSIt has confirmed that different socioeconomic characteristics, cultural aspects and education levels shape food safety perceptions within Eurasian countries. The COVID‐19 pandemic influenced their beliefs and trust in food safety, which is relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Moreover, food is perceived as a vital component of Indian culture and traditions which could be a contributory factor to such findings in India [26]. Additionally, it is evident that food safety concerns are more apparent in Asia compared with Europe, subsequently impacting food choice-related factors [27] as noted in our paper. In addition, the supermarket was the most popular food shopping location regardless of country.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, food is perceived as a vital component of Indian culture and traditions which could be a contributory factor to such findings in India [26]. Additionally, it is evident that food safety concerns are more apparent in Asia compared with Europe, subsequently impacting food choice-related factors [27] as noted in our paper. In addition, the supermarket was the most popular food shopping location regardless of country.…”
Section: Discussionsupporting
confidence: 54%
“…Boyadjieva and Ilieva-Trichkova (2015) found that higher levels of education were associated with higher levels of institutional trust. More educated consumers have higher levels of trust in all food system actors compared to less educated consumers (Tomasevic and Nikolic 2023).…”
Section: Educationmentioning
confidence: 97%
“…Consumers may also consider regulatory institutions to be indirectly responsible for food fraud incidents, as regulators failed to detect and prevent adulteration and conduct appropriate testing or checks (Kendall et al 2018). Tomasevic et al (2023) found that media representations of food fraud raised awareness of food fraud among consumer groups and meant consumers believed that food fraud was a food safety issue. Food fraud incidents may still have a negative impact on consumer trust among consumers that do not experience food fraud firsthand.…”
Section: Food Fraud and Risk Managementmentioning
confidence: 99%
See 2 more Smart Citations